Results and Problems in Cell Differentiation
DOI: 10.1007/400_2007_043
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Proton-Translocating FOF1-ATP Synthase

Abstract: H(+)-F(O)F(1)-ATP synthase catalyzes synthesis of ATP from ADP and inorganic phosphate using the energy of transmembrane electrochemical potential difference of proton (deltamu(H)(+). The enzyme can also generate this potential difference by working as an ATP-driven proton pump. Several regulatory mechanisms are known to suppress the ATPase activity of F(O)F(1): 1. Non-competitive inhibition by MgADP, a feature shared by F(O)F(1) from bacteria, chloroplasts and mitochondria 2. Inhibition by subunit epsilon in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 184 publications
1
49
0
1
Order By: Relevance
“…In agreement with this work, the structure of the γ-ε domain in the E. coli F 1 -ATP synthase [25] was found very similar to that of the isolated subunits [18]. Furthermore, it has been found that the ratchet mechanism of ε can be regulated by ATP binding in some bacteria [9,26]. When ATP is bound, the closed conformation is stabilized, thus favoring rotation of the central stalk in the ATPase direction; conversely, at low ATP concentrations, ε is unable to bind ATP, and therefore the extended conformation is favored, thus leaving the enzyme prone to rotate into the ATP synthase turnover.…”
Section: The Central Stalk Is Part Of the Atp Synthase Rotorsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with this work, the structure of the γ-ε domain in the E. coli F 1 -ATP synthase [25] was found very similar to that of the isolated subunits [18]. Furthermore, it has been found that the ratchet mechanism of ε can be regulated by ATP binding in some bacteria [9,26]. When ATP is bound, the closed conformation is stabilized, thus favoring rotation of the central stalk in the ATPase direction; conversely, at low ATP concentrations, ε is unable to bind ATP, and therefore the extended conformation is favored, thus leaving the enzyme prone to rotate into the ATP synthase turnover.…”
Section: The Central Stalk Is Part Of the Atp Synthase Rotorsupporting
confidence: 87%
“…The coupling between F 1 and F 0 is critical for efficient ATP synthesis to occur and major progress in the understanding of this coupling mechanism has been achieved. Several approaches at different laboratories showed that a central rotor actually gyrates relative to a stator that holds the catalytic subunits; this rotation induces the alternating binding, catalysis, and product release from three catalytic sites of F 1 (for reviews, see [5][6][7][8][9]). These studies also indicated that the γ subunit, together with ε and the ring of 9-15 c subunits of F 0 , form the rotor in the central part of the enzyme.…”
Section: Structure and Rotational Mechanism Of The Atp Synthasementioning
confidence: 99%
“…In addition the F 1 portion of F 0 F 1 can synthesize ATP when the rotor shaft is forced to rotate in a direction opposite that of ATP hydrolysis (11,12). It is well known that the ATP hydrolysis reaction catalyzed by both V-ATPase and F 0 F 1 is highly regulated by a number of different mechanisms to prevent wasteful ATP consumption (1,13). One such mechanism is Mg-ADP inhibition, whereby Mg-ADP binds into the catalytic site of the V 1 and F 1 domains and thus inhibits ATP hydrolysis (14 -17).…”
Section: Vacuolar-type Hmentioning
confidence: 99%
“…Subunit ε in bacterial F o F 1 has been known to be an intrinsic inhibitor of F 1 and F o F 1 complex (18,21,23) and is proposed to have a regulatory function (10,11,42). Although the inhibitory effects of subunit ε vary among species, in general, ε inhibits ATP hydrolysis activity while repressing ATP synthesis activity to a lesser degree (14,27).…”
mentioning
confidence: 99%